On an Alternative View to Complex Calculus - Sigaroodi, Sajedeh Norozpour (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
A review of complex calculus in use today, shows that new techniques to solve multivalued nature of logarithmic functions that cause lots of difficulties to work on this subject. One such techniques is re-orientation of complex space to the wider space B which will be explained completely in the following thesis. The aim of this study is to provide alternative complex calculus on multiplicative and bi-geometric cases. First of all, multiplicative complex calculus was accomplished, then, we found that there are still some drawbacks on this method, so bi-geometric case of complex calculus was established and the results showed that the mentioned drawbacks that are demonstrated in this study, do not appear in bi-geometric case. Further research is recommended to asses the Fourier series, Taylor polynomial and Laurent seried in bi-geometric complex calculus. Keywords: Newtonian Calculus, Bi-geometric complex calculus, Logarithm, Multiplicative complex calculus.

ÖZ: Günümüzde kullanımda olan karma¸sık kalkülüs (analiz yada hesap) incelemesi, logaritmik fonksiyonların çok degerli do ˘ gasını çözecek olan yeni tekniklerin, çok fazla ˘ zorluga neden oldu ˘ gunu göstermektedir. Bu tür tekniklerden birisi, ilerki kısımlarda ˘ detaylı bir ¸sekilde açıklanacak olan, daha geni¸s bir B’ye karma¸sık uzayin yeniden uyarlanmasidir. Bu çalı¸smadaki amaç, çarpımsal ve bi-geometrik durumlar üzerinde alternatif bir karma¸sık analizi saglamaktır. ˘ ˙Ilk olarak, çarpımsal karma¸sık analiz ba¸sarı ile gerçekle¸stirildi. Ancak daha sonra, bu yöntemde hala bazı sakıncalı durumların bulundugunu gördük, bu nedenle bi-geometrik karma¸sık matematiksel durumu(model) ˘ olu¸sturuldu, ve sonuçlar gösterdiki, Bi-geometrik durumda (modelde) daha önce gözlemlenen sakıncalı durumlar ortadan kalktı. Sonuç olarak gördük ki, bi-geometrik karma¸sık hesapta dizilen Fourier serileri, Taylor polinomu ve Laurent’i degerlendirmek ˘ için daha fazla ara¸stırma yapılması gerekir. Anahtar Kelimeler: Newton Analizi, Bi-geometrik karma¸sık hesabı, Logaritma, Çarpımsal karma¸sık hesap.
Doctor of Philosophy in Mathematics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2018. Supervisor: Prof. Dr. Agamirza Bashirov.
Keywords: Calculus--Functions of complex variables; Newtonian Calculus; Bi-geometric complex calculus; Logarithm; Multiplicative complex calculus; Mathematics